Visual Outcomes after Cataract Surgery in an Adult Patient with Presumed Amblyopia and Anisomyopia: Visual outcomes after cataract surgery - Gupta, Heena (Journal of Ophthalmic and Optometric Sciences, 2025)
Cataract surgery in adults with amblyopia can lead to improved visual acuity in the amblyopic eye, with several studies reporting a significant correlation between pre- and postoperative corrected distance visual acuity (CDVA). While some amblyopic eyes may experience a slight deterioration in visual acuity, many show stability or improvement after surgery. The extent of improvement varies, with some patients achieving 6/12 or better uncorrected visual acuity (UCVA) and nearly all achieving 6/12 or better best-corrected visual acuity (BCVA).